Onshore wind farms GIS-Assisted suitability analysis using PROMETHEE II. (November 2021) - Sotiropoulou, Kalliopi F.; Vavatsikos, Athanasios P.
Abstract: The increased use of renewable energy will reduce greenhouse gas emissions and comply with the European Union's commitment under the 2015 Paris Agreement on Climate Change. Wind energy generation contributes to the attainment of the Union's objectives because it is a mature and cost-effective national investment. Moreover, wind energy is part of the transition towards a circular economy primarily by producing clean renewable energy with a low environmental impact. The appropriate selection of both materials and sites is critical to ensure efficiency and low local impact. The selection of a wind farm installation site is a spatially complex decision-making problem that aims to evaluate alternative locations using planning and environmental restrictions. This paper introduces a new decision-making framework that combines geographic information systems (GIS) technology and PROMETHEE II, a multi-attribute decision making (MADM) method, to enable the GIS-assisted wind farm suitability analysis. The proposed framework can be used as a strategic planning tool that can help energy planners, wind developers, and decision and policy makers at the national and regional levels to accurately determine and predict the most efficient locations for wind farm development. The framework is illustrated through a case study of the Thrace region of north-eastern Greece. Highlights: Suitability analysis helps to avoid investments at inappropriate sites. A new framework that combines PROMETHEE II and spatial interpolation is proposed. The efficiency of the proposed framework is tested with the actual wind farms siting. Sensitivity analysis is implemented using Monte Carlo Simulation. The 13.20% of the examined area have a positive outranking character.